Strategi Diplomasi Publik Perancis pada UEFA Euro 2016 - Kenneth Ephram S; Alfian Farrel A.L; Ramadhan Dwi Setyawan; Siti Fatimah Jasmine; Ario Bimo Utomo (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
As part of France's efforts to build a positive national image in the eyes of the international community, this study examines the public diplomacy strategies employed by France during the Union of European Football Associations (UEFA) EURO 2016. France did not merely present UEFA EURO 2016 as a sporting event but also as an opportunity to leverage the occasion as a tool for public diplomacy to strengthen the country's ties with the global community and restore international trust following the 2015 terrorist attacks. The research analysis employs the framework introduced by Nicholas J. Cull, known as the Taxonomy of Public Diplomacy, which consists of five components: Listening, Advocacy, Cultural Diplomacy, Exchange Diplomacy, and International Broadcasting, using a qualitative research approach with a descriptive method. In the context of UEFA EURO 2016, France implemented all five elements of the taxonomy through the “Le Rendez-Vous” campaign, cultural promotion, and international media engagement, while reinforcing narratives of security and openness. The research findings indicate that France's public diplomacy strategy during the UEFA EURO 2016 event successfully strengthened the country's image as a tool of public diplomacy by using the sports competition as a diplomatic instrument to reach audiences worldwide. This study highlights the importance of sports as a tool of soft power in modern diplomacy.